RADIOIODINE THERAPY IN THYROID CARCINOMA AT RANGPUR,BANGLADESH - TAHER, M A (The ASEAN Journal of Radiology, 2023)
OBJECTIVE : To show the usefulness and success of small doses of radioiodine I131 in the treatment of well-differentiated thyroid carcinoma. MATERIALS & METHODS: Since 1990,in the small town Rangpur in North-west Bangladesh we are using radioactive iodine uptake (RAIU), isotope scanning ( I131 and Tc-99m) and ultrasonography of thyroid nodules.In 1998,we started radioassay of thyroid hormones (T3 & T4) and thyrotropin (TSH). About 6500 patients were tested for suspected thyroid problems. We have given post - thyroidectmy radioiodine therapy using small doses (Table 1) to six patients (M3,F3) with clinical improvements in the follow - ups. RESULTS: Initial results are encouraging as shown in Table 1. CONCLUSION : We feel broad-based long-term study should be done to optimize the dose schedule of radioiodine therapy.